Ultrabright dye-loaded spherical polyelectrolyte brushes and their fundamental structure-fluorescence tuning principles. Issue 29 (17th July 2019) - Masoomi, Hajar; Wang, Yao; Fang, Xiaoxia; Wang, Peirui; Chen, Cang; Liu, Kai; Gu, Hongchen; Xu, Hong
Abstract : A novel ultrabright fluorescent particle based on dye-loaded polyelectrolyte brushes is successfully established and the structure-fluorescence tuning principles are revealed. Abstract : Ultrabright fluorescent particles (UFPs) have attracted increasing attention because of their outstanding signal amplification functions. However, there is still an urgent demand for designing novel UFPs with new components or structures as the existing ones can not satisfy the practical requirements due to their inherent disadvantages. Here we propose a novel ultrabright fluorescent particle platform by doping dyes of 5-aminofluorescein (5-AF) into silica core-based spherical poly (acrylic acid) brushes (SiO2 @PAA@5-AF) and discuss their fundamental structure-fluorescence tuning principles. A series of brushes with different polymer chain lengths are successfully synthesized and then loaded with 5-AF through chemical binding. The high loading amount, suitable density or distribution, and enhanced quantum yield (QY) of 5-AF due to the amide bond formation with PAA chains on brushes are concluded as the three major reasons for the ultrabrightness of SiO2 @PAA@5-AF. Therefore, a 2350 ± 445 times brighter brush particle in comparison to a single quantum dot (QD) is realized, and a 2.1 ± 0.4 times fluorescence improvement of a brush vs . a QD normalized by volume is also achieved when taking the hydrodynamic diameter into consideration (∼300 nm vs . ∼30 nm). Moreover, the excellent tolerance stabilities in normally applied environments and outstanding label effects to form 4-plexed encoded beads are demonstrated as well. The results in this work strongly indicate a promising potential of SiO2 @PAA@5-AF as an ultrabright and stable signal amplification tool for biomedical related sensing, labeling, and biodetection.